Corporate social responsibility of developers in product perspective. case study: Johor Bahru - Tan, San San (2006)
This study deals with the implementation of Corporate Social Responsibility (CSR) in product perspective among the developers in the study area, Johor Bahru. For turning in good profits, the quality issues are inevitably sacrificed by most of developers as they rush to build and complete houses. Furthermore, there are over supply of unsold stock of completed properties in the housing market after economy recession. Today, developers are often at cross roads about the hard infrastructure they need to provide to satisfy the needs and wants of home buyers such as parks, garden and open space. Since there are remaining unsolved issues, more drastic action needs to be taken on critical housing projects and public awareness programmes especially to promote CSR among developers. Therefore, the objective of this study is to examine the implementation of CSR in product perspective by the developers and their impacts towards the township developments in Johor Bahru. In this study, four methodologies were employed: Questionnaire, the Customer Perspective of Balanced Scorecard Strategy Map, frequency approach and cross tabulation analysis. The questionnaire is designed by the measurement of Customer Perspective in Balanced Scorecard Strategy Map. The data collected are based on primary and secondary sources. In the process of the study, literature review is carried out by referring to the secondary sources of data that were be obtained and concluded from the previous studies, existing scholars work, journals, research papers and other sources such as property market report and published information from housing organization such as REHDA and House Buyers Associates (HBA). While, primary data will be derived from the interview with developers who have registered under REHDA based on random sampling method whereby 19 respondents will be taken from the total 50 developers located in Johor Bahru. The data collected will be analyzed through frequency approach and cross tabulation. Result of analysis tend to confirm the primary evidence from questionnaire survey whereby the effectiveness of CSR in product perspective implemented by developers by offering variety in product attributes to the community through the provision of security concept, well planned facilities and amenities have eventually shaped the township developments in Johor Bahru. Not all developers are affordable to complement CSR as company policy. Even, not all product attributes are contributed to CSR because it required a very strong financial capital to achieve CSR in product perspective. For those companies who have successfully implemented CSR in product perspective are those who have a very strong sales revenue recorded track and at the same time they have many on going sites projects development through the country. Usually these companies are belongs to public listed.